A Novel Synchronization-Based Approach for Functional Connectivity Analysis. (30th October 2017) - Lombardi, Angela; Tangaro, Sabina; Bellotti, Roberto; Bertolino, Alessandro; Blasi, Giuseppe; Pergola, Giulio; Taurisano, Paolo; Guaragnella, Cataldo
Abstract : Complex network analysis has become a gold standard to investigate functional connectivity in the human brain. Popular approaches for quantifying functional coupling between fMRI time series are linear zero-lag correlation methods; however, they might reveal only partial aspects of the functional links between brain areas. In this work, we propose a novel approach for assessing functional coupling between fMRI time series and constructing functional brain networks. A phase space framework is used to map couples of signals exploiting their cross recurrence plots (CRPs) to compare the trajectories of the interacting systems. A synchronization metric is extracted from the CRP to assess the coupling behavior of the time series. Since the functional communities of a healthy population are expected to be highly consistent for the same task, we defined functional networks of task-related fMRI data of a cohort of healthy subjects and applied a modularity algorithm in order to determine the community structures of the networks. The within-group similarity of communities is evaluated to verify whether such new metric is robust enough against noise. The synchronization metric is also compared with Pearson's correlation coefficient and the detected communities seem to better reflect the functional brain organization during the specific task.